Solar hydrogen energy systems : science and technology for the hydrogen economy - Zini, Gabriele; Tartarini, Paolo (Milan ; New York : Springer, 2012)
This volume provides the complete mathematical and chemical description of hydrogen used for storing and re-using the energy from renewable energies. The text also covers RENs, photovoltaics and wind, electrolyzers, hydrogen storage and fuel cells.
Introduction -- Hydrogen -- Electrolysis and Fuel Cells -- Solar Radiation and Photovoltaic Conversion -- Wind Energy -- Other Renewable Energy Sources for Hydrogen Production -- Hydrogen Storage -- Other Electricity Storage Technologies -- Study and Simulation of Solar Hydrogen Energy Systems -- Real-Life Implementations of Solar Hydrogen Energy Systems -- Conclusions.
engineering bookfair2015
Includes bibliographical references and index.
Description based on print version record.
Keywords: Renewable energy sources; Hydrogen as fuel; Electronic books